2014
DOI: 10.1007/s10753-014-9845-x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Honokiol on Sepsis-Induced Acute Kidney Injury in an Experimental Model of Sepsis in Rats

Abstract: Acute kidney injury (AKI) is a severe complication of sepsis, which largely contributes to the high mortality rate of sepsis. Honokiol, a natural product isolated from Magnolia officinalis (Houpo), has been shown to exhibit anti-inflammatory and antioxidant properties. Here, we investigated the effects of honokiol on sepsis-associated AKI in rats subjected to cecal ligation and puncture (CLP). We found that the administration of honokiol improved the survival of septic rats. Periodic acid-Schiff stain revealed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 52 publications
2
39
2
Order By: Relevance
“…The present study showed that honokiol significantly decreased the gene expression and activity of iNOS in the IRI rats. Previous studies have suggested that honokiol prevents the inflammatory response and the expression of iNOS in human osteoarthritis chondrocytes (33), and the level of iNOS is attenuated by honokiol in septic rats (34).…”
Section: Discussionmentioning
confidence: 91%
“…The present study showed that honokiol significantly decreased the gene expression and activity of iNOS in the IRI rats. Previous studies have suggested that honokiol prevents the inflammatory response and the expression of iNOS in human osteoarthritis chondrocytes (33), and the level of iNOS is attenuated by honokiol in septic rats (34).…”
Section: Discussionmentioning
confidence: 91%
“…In addition, reactive nitrogen species (RNS) is involved in sepsis-induced acute kidney injury [15,16]. Several studies showed that antioxidants alleviated sepsis-induced acute kidney injury [17,18]. Vitamin D is known for its classical functions in calcium uptake and bone metabolism [19].…”
Section: Introductionmentioning
confidence: 99%
“…This inventory was designed for individuals over 12 years old. Hopelessness, irritability, cognitions and physical symptoms, such as fatigue, weight loss and lack of sexual interest, are the main foci of the BDI-II 24 . Participants scoring 0–13 were classified as having no depression status; 14–19, light depression status; 20–28, medium depression status; and 29–63, severe depression status.…”
Section: Methodsmentioning
confidence: 99%